(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
Plant communities of windbreak forest strips in the Middle Dnieper region are studied. Their diversity requires a new syntaxonomic solutions due to significant difference from natural plant communities. The syntaxonomy based on the identified coenotic influence of planted tree species within windbreak strips. It was developed after descriptions of the entire species in communities including typical ruderal species that optimally exist in this environment, species of natural forests and shrubs that have acquired the ability to survive in these conditions. The alliance Sambuco nigrae-Quercion robori and three association Alliario petiolatae-Ptelietum trifoliatae, Elytrigio repentis-Quercetum robori, Sambuco nigrae-Quercetum robori belong to the basic order Chelidonio-Robinietalia pseudoacaciae with synanthropic shrub vegetation were described as new for science. Moreover, three association Poo nemoralis-Tilietum cordatae, Geo urbano-Fraxinetum and Balloto nigrae-Ulmetum within Geo-Acerion platanoides were provided as ass. nova prov. Phytocenoses that marked a new rank syntaxons, are the result of the spontaneous formation of ecosystem populations of allochthonous and autochthonous species of the regional flora of the Forest-Steppe of Ukraine under the conditions of the edificatory effects of artificially created trees stands. The peculiarities for all identified and newly described syntaxa are presented.